2021
DOI: 10.3389/fpsyg.2020.607621
|View full text |Cite
|
Sign up to set email alerts
|

Individual Chunking Ability Predicts Efficient or Shallow L2 Processing: Eye-Tracking Evidence From Multiword Units in Relative Clauses

Abstract: Behavioral studies on language processing rely on the eye-mind assumption, which states that the time spent looking at text is an index of the time spent processing it. In most cases, relatively shorter reading times are interpreted as evidence of greater processing efficiency. However, previous evidence from L2 research indicates that non-native participants who present fast reading times are not always more efficient readers, but rather shallow parsers. Because earlier studies did not identify a reliable pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 83 publications
3
11
0
Order By: Relevance
“…The present data thus support a view in which increasing chunking ability is directly associated with sensitivity to the regularities in the input: this may either result in facilitation, where linguistic patterns are predictable (NP2 attachment); or in increased relative costs, where expectations run counter to the incoming signal (NP1 attachment). This view fits well with previous evidence of the effect of chunking ability on second language processing (Pulido, 2021;Pulido et al, under review); but while lack of sensitivity in non-native speakers could be attributed to lower linguistic proficiency or to greater processing demands (Hopp, 2013), none of those factors would apply here. The results add an important dimension to previous work that reported variability during native language processing by associating said variability to individuals' chunking ability.…”
Section: Discussionsupporting
confidence: 92%
“…The present data thus support a view in which increasing chunking ability is directly associated with sensitivity to the regularities in the input: this may either result in facilitation, where linguistic patterns are predictable (NP2 attachment); or in increased relative costs, where expectations run counter to the incoming signal (NP1 attachment). This view fits well with previous evidence of the effect of chunking ability on second language processing (Pulido, 2021;Pulido et al, under review); but while lack of sensitivity in non-native speakers could be attributed to lower linguistic proficiency or to greater processing demands (Hopp, 2013), none of those factors would apply here. The results add an important dimension to previous work that reported variability during native language processing by associating said variability to individuals' chunking ability.…”
Section: Discussionsupporting
confidence: 92%
“…Chunking complex sentences into clauses, for example, may help learners process their structure, while smaller chunks like adjective-preposition pairs can raise awareness of collocations such as interested in. Eye-tracking research by Pulido (2021) has demonstrated that L2 readers who chunked while reading were more efficient readers. However, chunking alone is not likely to improve comprehension; it is necessary to accurately connect and parse the relationships between chunks to form meaning (Nishida, 2013).…”
Section: Input Enhancement and Chunkingmentioning
confidence: 99%
“…The rapid increase in the use of eye-tracking methodology has been based on the “eye-mind assumption” that posits a tight link between human eye gaze and the focus of attention (Just & Carpenter, 1980 ). However, this assumption has been challenged by several studies in the literature (e.g., Kliegl et al, 2006 ; Mitchell et al, 2008 ; Schindler & Lilienthal, 2019 ), although the exact nature of the eye-mind relationship remains debatable (Pulido, 2021 ; Sharafi et al, 2020 ; Strohmaier et al, 2020 ). Previous eye-tracking studies of text reading (Rayner, 1978 , 1998 ) have established a number of informative eye-movement features, including fixation (50–1500 ms pause of visual gaze on a segment), saccade (quick movement between two phases of fixations in the same direction), and regression (backward saccade to a previously visited segment).…”
Section: Introductionmentioning
confidence: 99%